The effect of personality traits on online privacy concern - Škrinjarić, Bruno (Array, 2018)
This paper examines personality traits as antecedents of online privacy concern. The aim of the research is to analyze if and how personal characteristics of Internet users affect their concern for privacy in online environment. The theoretical framework consisting of the Big Five theory of personality traits has been used to test the variations in online privacy concern. The model includes a range of other variables that might affect online privacy concern, such as sociodemographic factors, cultural values and computer literacy. The empirical analysis is based on survey data collected in 2016 on a large sample of 2,060 Internet users in Croatia. Results of bothOLS and ordered probit estimations show that two personality traits dimensions, namely extraversion and neuroticism, signifi cantly determine the level of online privacy concern. The more extraverted, i.e., more energetic and outgoing Internet user is less concerned about his/her online privacy, whilst the more neurotic one is more concerned. Privacy awareness, computer anxiety and previous negative experience were also observed as antecedents, all positively affecting the level of privacy concern of Internet users. The results of this research fi ll the gap in the underexplored area of personality traits and onlineprivacy concern literature and contribute to developing an extended model of online privacy concern.